Transesterification of High Free Fatty Acid Jatropha Curcas Oil using Heterogeneous Catalyst - Mythili, R; Venkatachalam, P; Subramanian, P; Uma, D (Journal of Agricultural Engineering, 2013)
Biodiesel is a cleaner burning diesel alternative fuel produced from vegetable oils and fats throughtransesterification process. Jatropha curcas oil used for biodiesel production had free fatty acid content of 8.8per cent. The oil was pretreated using sulphuric acid with 25% methanol for 1 h at 50Â°C. The yield of pretreatedoil was 95% and the FFA content was reduced. The acid treated oil was transesterified using 0.5% NaOH and25% methanol for 2 h at 60Â°C. The yield of monoester was 95.8 per cent.